1963
DOI: 10.2307/2333782
|View full text |Cite
|
Sign up to set email alerts
|

Tables of Integrals and Other Mathematical Data.

Abstract: Abscissa of convergence 403 Active filter circuits 353, 359, 361 Admittance 344, 366, 485, 495 Aliasing 228, 229, 452 Aliasing (eliminating it) 235 Allpass digital filter 307 Allpass digital filter (1st-order) 449 Allpass digital filter (2nd-order) 450

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
84
1
6

Year Published

1965
1965
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 367 publications
(92 citation statements)
references
References 0 publications
1
84
1
6
Order By: Relevance
“…By using (5.2), (5.3), and the well-known results (e.g., [29], Sections 21.4 and 22.3 of Chapter V, [30], 440.11), one can show that the expansion is…”
Section: Exact Analytical Expression For the Steady-state Stressmentioning
confidence: 93%
“…By using (5.2), (5.3), and the well-known results (e.g., [29], Sections 21.4 and 22.3 of Chapter V, [30], 440.11), one can show that the expansion is…”
Section: Exact Analytical Expression For the Steady-state Stressmentioning
confidence: 93%
“…Noting from Figure 2.1 that 3.34, and 3.35 constitute the exact formal solution for the fields generated by the charge separation process and the accompanying current flow. The quantities Rf and Of may be found in terms of zf using Equations 2.7 and 3.22, while zf can be found as a function of t by inverting the time-distance quation (Equation 2.10) as discussed in Appendix A.…”
Section: S(321)mentioning
confidence: 99%
“…This integral is readily evaluated using standard forms, (for example Dwight 3 Items 90.1 and 92.1) and after some algebraic reduction it is found that…”
Section: -1mentioning
confidence: 99%
“…(16)-(18), we establish the formal relation between the  m and  t (19)Since the elements dS, dS m , dS t form a right-angled triangle, it can be reasoned that With allowance for the trigonometric relations in[7…”
mentioning
confidence: 99%